2017
DOI: 10.1007/s10072-017-2946-1
|View full text |Cite
|
Sign up to set email alerts
|

Can both normal and mildly abnormal albuminuria and glomerular filtration rate be a danger signal for diabetic peripheral neuropathy in type 2 diabetes mellitus?

Abstract: We aimed to investigate the potential association between urinary albumin-to-creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR) and diabetic peripheral neuropathy (DPN). We were especially interested in the relationship between normal or mildly abnormal UACR and eGFR with DPN. A retrospective study was performed in 1059 patients with type 2 diabetes patients from Fuzhou, China, who were seen between 2010 and 2015. The DPN population demonstrated higher UACR and lower eGFR than the non-DPN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…These results are consistent with the findings of our study in showing a close correlation between albuminuria and the occurrence of DPN. Moreover, a very recent retrospective study [ 33 ] also found an association between elevated UACR and decreased eGFR and DPN. Although the results of our study are similar to those reported earlier, the overall design of our study was different, and our analysis of risk factors leading to abnormal SWMT and VPT test results may add to the reliability of results.…”
Section: Discussionmentioning
confidence: 93%
“…These results are consistent with the findings of our study in showing a close correlation between albuminuria and the occurrence of DPN. Moreover, a very recent retrospective study [ 33 ] also found an association between elevated UACR and decreased eGFR and DPN. Although the results of our study are similar to those reported earlier, the overall design of our study was different, and our analysis of risk factors leading to abnormal SWMT and VPT test results may add to the reliability of results.…”
Section: Discussionmentioning
confidence: 93%
“…Insulin resistance causes impaired insulin signalling, primarily leading to inhibition of the phosphoinositide 3-kinase (PI3K)/Akt signalling pathway, which in turn results in injury to the nervous systems. UACR, a potent indicator for diabetic nephropathy, is closely associated with DPN [ 44 ]. DPN may be driven or accompanied by diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study from China has also demonstrated that increased HbA1c variability adds to poor chronic glycemic control and is closely associated with diabetic neuropathy in patients with type 2 diabetes (Su et al, 2018). Lower eGFR and higher UACR may be associated with increased risk of DPN even though normal or mildly abnormal UACR and eGFR have already been found to be predictive factors of diabetic neuropathy (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%